2014
DOI: 10.1093/trstmh/tru050
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological patterns of mortality due to visceral leishmaniasis and HIV/AIDS co-infection in Brazil, 2000–2011

Abstract: VL-HIV/AIDS co-infection is an increasing public health problem in Brazil. The systematic description of the epidemiological characteristics and magnitude of mortality related to VL-HIV/AIDS co-infection reflects the need to intensify control measures and disease surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 23 publications
1
28
1
6
Order By: Relevance
“…There was no difference from other studies and it probably reflects the proportion of HIV cases between men and women in the general population. 9,15,22,23 Gil-Prieto et al, 24 in Spain, observed that 90% of the HIV/leishmaniasis coinfected individuals were aged between 25 and 49 years, not so far from the 75% in our study in the same age group. This is an important aspect because that is an economically active age.…”
Section: Visceral Leishmaniasis In Hiv-infected Patients In Brazilcontrasting
confidence: 60%
“…There was no difference from other studies and it probably reflects the proportion of HIV cases between men and women in the general population. 9,15,22,23 Gil-Prieto et al, 24 in Spain, observed that 90% of the HIV/leishmaniasis coinfected individuals were aged between 25 and 49 years, not so far from the 75% in our study in the same age group. This is an important aspect because that is an economically active age.…”
Section: Visceral Leishmaniasis In Hiv-infected Patients In Brazilcontrasting
confidence: 60%
“…Currently, HVL is one of the most serious public health problems in Brazil, mainly owing to its geographical expansion, especially to nonendemic areas, as well as increased morbidity and mortality 10 , which are directly related to the precarious socioeconomic and health conditions of the population. Therefore, in addition to control measures that have already been implemented, it is necessary to take actions that go beyond the health field, guaranteeing resolution in the face of inequities in access to education, living conditions, food, and livelihoods, as well as providing environmental improvements such that a real impact on the occurrence of HVL is achieved 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Mesmo diante da redução da prevalência da doença de Chagas em todo o território brasileiro, em decorrência da eliminação do seu principal vetor, o Triatoma infestans, e do controle da transmissão transfusional (segunda via de transmissão em ordem de importância, depois da vetorial), a situação na Região Nordeste brasileira ainda é preocupante, principalmente por três motivos: concentra a maior quantidade de vetores secundários implicados na transmissão da doença, de especial importância o Triatoma brasiliensis, cujos hábitos peridomiciliares dificultam a sua localização, captura e controle químico por inseticidas; a região mantém altos índices de más condições de moradia, apropriados à colonização pelo triatomíneo; as medidas de fiscalização e controle entomológico não têm sido eficazes 1,2 .…”
Section: Introductionunclassified
“…Nos últimos anos foram desenvolvidos estudos de base populacional que evidenciaram a ocorrência da endemia em diversos estados brasileiros e, principalmente, no Piauí 2,3,4 . O último inquérito sorológico realizado nesse estado, em 2002, entre pessoas residentes na zona rural, mostrou prevalências que chegaram a 11,6% de sororreatividade em algumas localidades, valor superior ao dobro dos valores estimados para o estado em inquérito nacional realizado 20 anos antes.…”
Section: Introductionunclassified